TSJC orchestras play this week (Raton Range Raton, New Mexico, 1990)
This article is about the Trinidad State Junior College announcing its annual spring performance schedule.
Newspaper article + Photograph of Madonna McGowan
Mater List Item # 11
File location is in the Raton File Cabinet
Keywords: McGowan, Madonna; Malin, Don; Trinidad State Junior College; Chamber Orchestra; Musical Performances; Orchestras; Live Music; Raton, New Mexico; Trinidad, Colorado